FREEDOM VS STABILITY: DILEMMA OF POSTCOMMUNIST DEVELOPMENT - Романюк, О.І. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2015)
The task bringing to light the leading postcommunist transformations tendencies is laid down in this article. The author, making conclusion that these are liberalization and consolidation of political regimes, turns one’s attention to contradictory character of their interaction. The solution of postcommunist development dilemma, which give rise to the contradiction between the freedom and stability, is creation of defence capacity democracy.